Thermodynamics and Adsorption of Fe2+ from Oilfield Produced Water using Clay-derived Zeolite - Osuala, Kingsley Ifeanyi; Okewale, Akindele Oyetunde (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
The study explored the potential of clay-derived zeolite (CDZ) as an adsorbent for the removal of Fe2+ ions from produced water generated from oil fields. The clay was sourced from the Ikepshi Community in the Akoko-Edo Local Government Area of Edo State, Nigeria. The zeolite was produced through a calcination process at a temperature of 600 °C, followed by dealumination and zeolite synthesis prior to its application for adsorption of Fe2+ from produced water. A variety of operational parameters were evaluated to understand their impacts on the adsorption process. These included different dosages of the adsorbent, contact time, temperature, agitation speed, and pH levels. The thermodynamics parameters were evaluated over a temperature range of 303 K to 343 K. Scanning Electron Microscopy (SEM) images displayed the characteristic silicate flakes of kaolinite clay, while Fourier Transform Infrared Spectroscopy (FTIR) results identified specific functional groups. Particularly, the presence of O-H and Si-O stretching vibrations confirmed the clay kaolinite composition. The analysis of adsorption outcomes across varying temperatures revealed negative values for Gibbs free energy ( ), and a positive entropy value ( , this indicates that the adsorption process is spontaneous and feasible, along with an increase in degree of randomness of adsorption process. The process of Fe2+ uptake on CDZ was considered as endothermic, as shown by the positive enthalpy values ( obtained thus shows a strong Vander Waal forces between the adsorbent and adsorbate.